Dissemination of Household Waste Processing into Eco-Enzyme Products - Eva Astuti Mulyani; Ahmad Fauzan Alghifary; Asshhiyami Zikra; Fitri Wahyuni; Hafizahtul Khairat Abbas; Nadia Yulisa; Nurul Finasty; Nurul Afifah Oktavia; Rista Syahrida; Satria Perdana; Satria Vannani Ardi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
One of the environmental problems that occur in each region is the problem of waste. The waste produced by every household is certainly something, whether it is organic waste or inorganic waste. Organic waste that is not managed properly will cause global warming (global warming). Besides that, it can also cause potential health hazards such as diarrhea, cholera, typhus, and dengue fever due to viruses, bacteria, or fungi. We are seeing the potential for organic waste in Ganting village, where the livelihoods of the people there are generally vegetable and fruit farmers, such as spinach, kale, corn, and others. Efforts that can be made to reduce the negative impact of residual organic matter in Ganting village are socialization regarding the processing of food waste into more useful products, namely